2008
DOI: 10.1021/ac8011297
|View full text |Cite
|
Sign up to set email alerts
|

ABTS-Modified Multiwalled Carbon Nanotubes as an Effective Mediating System for Bioelectrocatalytic Reduction of Oxygen

Abstract: The ability of such a common redox mediator as 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) to undergo sorption on carbon surfaces is explored here to convert multiwalled carbon nanotubes (CNTs) into a stable colloidal solution of ABTS-modified carbon nanostructures, the diameters of which are approximately 10 nm (as determined by transmission electron microscopy). Subsequently, inks composed of fungal laccase (Cerrena unicolor) mixed with the dispersion of ABTS-modified CNTs and stabilized with Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 35 publications
8
54
0
1
Order By: Relevance
“…This three-dimensional composite material (3D-CNT/CMF) was recently fabricated [8] and utilized in bioelectrocatalysis of horseradish peroxidase (HRP) for H 2 O 2 reduction at +600 mV vs. Ag|AgCl [9]. The main advantages for using the 3D-CNT/CMF composite electrode as immobilization surface for laccase consists on: i) avoiding the use of a redox hydrogel film as matrix for the electronic communication between enzyme and electrode, thus eliminating additional limitations such as the electron hopping step [10] and a further drop in the cell potential [11][12][13]; and ii) reduction of the large number of interfacial cascades in-between the individual CNT produced when they are simply dropped onto a supporting electrode in presence or not of a mediator/crosslinking polymeric net [14][15][16], which requires extensive optimization protocols and characterization methods, such as SECM [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This three-dimensional composite material (3D-CNT/CMF) was recently fabricated [8] and utilized in bioelectrocatalysis of horseradish peroxidase (HRP) for H 2 O 2 reduction at +600 mV vs. Ag|AgCl [9]. The main advantages for using the 3D-CNT/CMF composite electrode as immobilization surface for laccase consists on: i) avoiding the use of a redox hydrogel film as matrix for the electronic communication between enzyme and electrode, thus eliminating additional limitations such as the electron hopping step [10] and a further drop in the cell potential [11][12][13]; and ii) reduction of the large number of interfacial cascades in-between the individual CNT produced when they are simply dropped onto a supporting electrode in presence or not of a mediator/crosslinking polymeric net [14][15][16], which requires extensive optimization protocols and characterization methods, such as SECM [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Fe 3 O 4 nanoparticles were treated with aminopropyltriethoxysilane and subsequently dropped on the PDC/GC electrode to form a composite film. This modified electrode showed an enhanced effective surface area and increased electrocatalytic activity towards the oxidation of NAD(P)H. Besides the oxidation of NAD(P)H, mediators have been immobilized for the reduction of oxygen (Ganesan and Ramaraj 2000;Karnicka et al 2008;Nogala et al 2006), the detection of hydrogen peroxide (Liu et al 1997;Siao et al 2011), or without any application relation (Pauliukaite et al 2009). …”
Section: Doumèche and Blummentioning
confidence: 99%
“…(Habrioux et al, 2010) Previous studies have shown the interest lying in the use of ABTS 2-as redox mediator in combination with multicopper oxidases. One of them was carried out by Karnicka et al who have shown that wiring laccase to glassy carbon through a ABTS 2-/carbon nanotube system was a very efficient pathway to reduce molecular oxygen into water (Karnicka et al, 2008). The combination of ABTS 2-with BOD is also known to exhibit a high electrochemical activity towards oxygen reduction reaction (Tsujimura et al, 2001).…”
Section: Reduction Of Oxygen Catalyzed By Bilirubin Oxidasementioning
confidence: 99%